Regression-Correlation of Petrophysical Inter-Parameter of Igneous Rocks and Limestone from Kulonprogo Mountain Region, Yogyakarta Special Region - Maryanto, Sigit; Hasan, R. (Geological Agency, 2011)
DOI:Â 10.17014/ijog.v6i4.127Laboratory test of complete petrophysic parameters encompasing water absorption, compressive strength, Los Angeles abrasive strength, Rudellof abrasive strength, and wear resistance with Na2SO4 has been carried out for igneous and carbonate rocks taken from Kulonprogo Mountains region. Statistical verification of the data exhibits variation of correlation coefficients among parameters ranging from medium to very high value. The values of petrophysic test results are determined by the rock types. The result of this study is useful to estimate the accuracy of values of each parameter test result in Geological Survey Institute Laboratory using regression formula representing each relationship.